The use of alpha-fetoprotein for detecting hepatocellular carcinoma may potentially be more beneficial for patients with aggressive hepatocellular carcinomas and high alpha-fetoprotein levels - Waraporn Panjawong (2019)
© 2018, Medical Association of Thailand. All rights reserved. Objective: There is some controversy as to whether alpha-fetoprotein [AFP] should be used in screening for hepatocellular carcinoma [HCC] or not. Materials and Methods: Data from our hospital HCC registry 2010 to 2014 were retrospectively analyzed. Asymptomatic patients with HCC who were diagnosed by AFP alone (where ultrasound [US] did not detect a lesion or trigger a diagnostic test) were compared with patients detected by US. Results: Out of 314 patients in the registry, 43 patients were diagnosed without symptoms. US detected 33 patients with HCC, while 10 patients (equal to 23.3% of the total or 30% additional patients) were detected by AFP alone. These patients were younger, had higher median AFP level and were at a better BCLC stage than those detected by US. The treatment outcomes for these patients were no different from the US detected patients, whether in terms of death, local tumor control or recurrence. Conclusion: The use of AFP in addition to US allowed earlier detection in 30% more patients than if US was used alone. These patients had higher AFP but achieved the same outcomes as those in the US detected group who had lower AFP. The use of AFP in screening may therefore be of particular benefit in terms of early detection and treatment for those patients with the more aggressive HCC with high AFP.